Berechnung:
d<sub>dk</sub> = (p / π) * × z<sub>k</sub>
d<sub>dk</sub> = (5mm / π) * × 38
d<sub>dk</sub> = 60,48mm 48 mm
d<sub>dg</sub> = (p / π) * × z<sub>g</sub>
d<sub>dg</sub> = (5mm / π) * × 114
d<sub>dg</sub> = 181,44mm44 mm
L´<sub>d</sub> = (2 * × e´)+ [(π/2 * ) × (d<sub>dg</sub> + d<sub>dk</sub>)) ] + ([(d<sub>dg</sub> – d<sub>dk</sub>)² / (4 * × e´ )]
L´<sub>d</sub> = (2 * × e´)+ [(π/2 * ) × (181,44mm 44 mm + 60,48mm)48 mm) ] + ([(181,44mm 44 mm – 60,48mm48 mm)² / (4 * × e´ )]
L´<sub>d</sub> = 973mm
Änderungen – BS-Wiki: Wissen teilen
Änderungen
76 Byte hinzugefügt,
10:57, 31. Mai 2006